Intraseasonal Variability of Air Temperature Over East Asia in Boreal Summer - Zhao, Chen; Li, Tim; Yao, Suxiang; Behera, Swadhin K.; Nasuno, Tomoe (Frontiers in Earth Science, 2017)
The intraseasonal oscillation (ISO) of atmospheric temperature at 2 m over East Asia (EA) in boreal summer is investigated through NCEP-NCAR reanalysis data for the period of 1979–2013. It is found that the surface air temperature in EA propagates on a 10–30-day time scale and exhibits a southeastward propagation characteristic. The average zonal and meridional phase speed of the intraseasonal air temperature anomaly is about 2.6° longitude and 1.7° latitude per day, respectively. The advection by the mean wind and the advection of the summer mean temperature by the intraseasonal wind primarily contribute to the propagation of the intraseasonal temperature perturbation through the diagnosis of the temperature budget. An upper-tropospheric geopotential positive (negative) height anomaly is closely associated with a low-level warmer (cooler) air temperature anomaly and both anomalies propagate southeastward in a similar way. A wave activity flux analysis reveals that mid-latitude Rossby wave energy also propagates southeastward, consistent with the upper-tropospheric geopotential height propagation. This indicates that in addition to low-level advection mechanism, upper-tropospheric forcing through the hydrostatic relationship is another possible mechanism. A further statistical analysis indicates that heat waves in EA summer are modulated by the southeastward-propagating intraseasonal temperature mode.